Knowledge Sharing Pattern Among the Arts Faculty Students of Dhaka University: A Survey - Islam, Shariful; Nowrin, Shohana; Mostofa, Sk. Mamun (DESIDOC Journal of Library & Information Technology, 2017)
The purpose of this paper is to explore the Knowledge Sharing (KS) patterns among the students of the Arts faculty, University of Dhaka (DU). In order to investigate the KS patterns, a structured questionnaire was used which included different parameters such as background information of the respondents, their purpose, frequency, preferred channels, benefits and motivators for Knowledge Sharing. The data were collected from a total number of 372 students and later analysed using SPSS and Microsoft Excel. The study revealed that, majority of the students of the Arts faculty share their knowledge for self-satisfaction. Although, largest numbers of the students also believe knowledge sharing help them to create new knowledge and ideas, while, learning from each other is their prime motivator for KS.